Study on Control Strategies for the Multilevel Cascaded Converters - Lin Xu; Yang Han (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The multilevel cascaded converters are extensively applied for high-voltage and high-power applications, which are considered as the most favorable topologies for the high power ac-drives and the high-voltage DC transmission (HVDC) systems using the voltage source converters (VSCs). This paper presents the dc capacitor balancing and effective current regulation methodologies for the multilevel cascaded converters. The dc-link voltage balancing and capacitor energy evolving mechanism of the MMCC is analyzed, and an effective control scheme is devised by utilizing two dc capacitor voltage control loops, including the total capacitor voltage controller (TCVC), the capacitor voltage balancing controller (CVBC). The predictive current controller is proposed to enhance the tracking accuracy of current control loop. The proportional-resonant controller (PRC) is used as circulating current damping controller of the modular multilevel converter, which is found to be highly effective to minimize the circulating current. The Electromagnetic Transient Program (EMTP) is utilized for digital simulation of the single-phase five-level modular multilevel converter. The effectiveness of the control scheme is validated by the simulation results. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.2994